The Influence Of Product Quality, Price And Service On Customer Satisfaction At Lesehan 123 Jamik Bengkulu City - Kusumo Edo Utomo; Karona Cahya Susena; Nirta Vera Yustanti (Journal of Indonesian Management, 2023)
Service or service issues also determine development business in business. Good service and as expected will give satisfaction to consumers. This study aims to determine the effect of product quality, price and service quality on consumer satisfaction at Lesehan Jamik, Bengkulu City. At the present time marketing using product quality improvement, affordable prices and quality service. This study uses quantitative research methods, the population in this study is consumers, through a given questionnaire.The technique in taking the research sample using the accidental sampling technique is a technique of determining a sample based on chance, the sample in this study was 120 customers at Lesehan Jamik 123 Kota Bengkulu. Data collection used instruments in the form of questionnaires and the analytical method used was multiple linear regression, determination test and hypothesis testing. Research Results There is a positive and significant influence between Product Quality on Consumer Satisfaction at Lesehan Jamik Bengkulu City, which means that the better the product quality, the more Customer Satisfaction will be increased. There is a positive and significant influence between price and consumer satisfaction at Lesehan Jamik, Bengkulu City, which means that the affordable price of a product will increase customer satisfaction. There is a positive and significant influence between Service Quality on Customer Satisfaction, which means that the better the service quality, the higher the customer satisfaction. There is a positive and significant influence between Product Quality, Price and Service Quality on Customer Satisfaction that the better the product quality, price and service quality, the more people or consumers talk about the superiority of a product.